Використання евристичних алгоритмів в інформаційних системах логістики міжнародних транспортних перевезень - Черноволов, В. (ХНУРЕ, 2023)
This work is devoted to the evaluation of heuristic algorithms used in the information systems of international transport logistics. These algorithms play an important role in solving complex optimization and planning problems related to routes, schedules, transportation costs, product placement, and other aspects of logistics. The main goal of the work is to analyze and compare various heuristic algorithms in order to determine their effectiveness and suitability for use in various scenarios of international transportation. The work also includes an analysis of the limitations and potential shortcomings of these algorithms, and explores opportunities to improve their performance using machine learning and artificial intelligence